Sandton City : looking for a sustainable power solution - Townsend, Stephanie ([London] : SAGE, 2016)
In May 2008, Johannesburg's Sandton City shopping complex was on the road to recovery from its experience that January, when it was hit hardest of all shopping centres in the country by Eskom's random power cuts. Sandton City general manager, Gary Vipond, and Dorcas Ledwaba, the director of property management at Liberty Life Properties, which owns the complex, had managed to find ways of saving electricity, and had put a solution in place involving generators and inverters. Planned power cuts had taken place for a short period in April, but Eskom had since announced that it would cease planned power cuts and would try to provide continuous power. Yet the two knew that the electricity situation was still critical.
Originally Published in: Townsend, S. (2008). Sandton City: Looking for a Sustainable Power Solution. WBS-2008-6. Johannesburg: The Case Centre, Wits Business School.
Description based on online resource; title from home page (viewed on May 5, 2016).
Keywords: elektronické knihy; electronic books; Shopping centers -- Management -- Case studies; Electric power failures -- Economic aspects -- South Africa -- Case studies